2019
DOI: 10.1007/s10459-019-09879-4
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional practice: beyond competence

Abstract: Interprofessional practice is commonly discussed in the literature in terms of competencies. In this study we move away from the theoretical notions of criteria, concepts and guidelines to adopt an ontological approach which seeks to stay as close to the lived experience as possible. Our research asked 12 participants from a variety of health disciplines to tell their stories of working interprofessionally. We sought to glean meaning from the lived experience. Our phenomenological hermeneutic approach and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 27 publications
1
13
0
2
Order By: Relevance
“…Harmonisation can bind distinct professionals and potentially opposing forces. Consistent with literature highlighting respect, trust, and the mutual acknowledgement of professional roles as conflict reducing factors [ 9 13 ], this study’s findings demonstrate how such harmonising elements function to connect team members. For example, when asked how the team members worked together despite professional differences, several informants emphasised the ability to learn and being responsive to the perspectives of other professions as an important factor in being a ‘trustworthy team member’.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Harmonisation can bind distinct professionals and potentially opposing forces. Consistent with literature highlighting respect, trust, and the mutual acknowledgement of professional roles as conflict reducing factors [ 9 13 ], this study’s findings demonstrate how such harmonising elements function to connect team members. For example, when asked how the team members worked together despite professional differences, several informants emphasised the ability to learn and being responsive to the perspectives of other professions as an important factor in being a ‘trustworthy team member’.…”
Section: Resultssupporting
confidence: 86%
“…Similarly, according to McDonald et al [ 12 ], respectful interactions based on trust promoted interprofessional collaboration. Lastly, Flood et al [ 13 ], found that interprofessional work flourished when professionals were open and responsive to the situation and each other.…”
Section: Introductionmentioning
confidence: 99%
“…Isso acontece por meio de práticas reflexivas intencionais, que promove o desenvolvimento da empatia, um componente crítico ausente dos modelos de formação e de prática profissional atuais. A prática interprofissional floresce quando os profissionais são autênticos, empáticos, cuidadosos e valorizam a pessoa mais do que a técnica 19,20…”
Section: Identidade Profissional Adquirida Pelo Sistema De Saúde Por ...unclassified
“…Neste sentido, essa sensação do outro estimulará os profissionais a tomarem decisões com mais rapidez e de forma mais assertiva, com grandes benefícios nos períodos de epidemia/pandemia, que exigem dinamismo nos diagnósticos e terapêuticas. O trabalho interprofissional em saúde durante o primeiro ano da pandemia de COVID-19 confirmou a importância do trabalho interprofissional e suas dimensões para a prestação de serviços mais abrangentes, mais resolutivos e mais seguros [19][20][21] .…”
Section: Mudanças No Processo De Trabalho Influenciadas Pela Eipunclassified
“…Similarly, after examining the collaboration between health professionals, both Pullon (11) and McDonald et al (12) found that respect, trust, and shared values and goals were important criteria for e cient collaborative work. Further, by analysing various health professionals' stories of interprofessional work, Flood et al (13), observed that such work ourished when professionals were open and responsive to the situation and each other.…”
Section: Literature Reviewmentioning
confidence: 99%